The status of the mobile phone number as general purpose identifier – elaboration on cases from Norway and Pakistan - Hanne Kristine Hallingby (International Telecommunications Society (ITS), 2016)
This paper discusses the mobile number's status as a general purpose identifier in digital customer journeys. The strength and availability of the mobile number as ID is assessed across several markets and examples of use are given. Two cases where the mobile number already is a trusted resource and installed base are presented. Strength and availability for the mobile number as ID varies across markets depending on ID requirements for SIM-cards and the local ecosystem: some markets score high, others low. The cases discussed are Norway and Pakistan. They are respectively a developed and developing economy however; both demonstrate a strong and available mobile number and innovative uses in digital customer journeys. This signals on the one hand a potential universal applicability of the mobile number across markets with very different prerequisites, on the other hand that use of the mobile number is a local phenomenon only. The analysis indicates that across markets there is an ongoing and continuous management of both mobile numbers and other IDs in order to affect strength and availability, to reach a sufficient installed base, and position as an attractive resource for digital customer journeys.
Keywords: 330